Ironiens tænker, tænkningens ironi (Vol. 12):Kierkegaard læst retorisk - Jacob Bøggild (Teori og æstetik, 2004)
Kierkegaard is not only a thinker writing about and practising irony. He is also conscious of the irony of the very notion of thinking. Taking his departure in Kierkegaard's (), Bøggild shows how style is the constituting element of content in Kierkegaard's writings and clarifies what Kierkegaard meant by saying that his works were indirectly communicated and retracted. Jacob Bøggild, PhD, is a lecturer in the Department of Scandinavian Languages and Literatures at the University of Aarhus.